The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/molecules26206198
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Thermal Stability of Ionogels: Synthesis and Properties of Triple Ionic Liquid/Halloysite/MCC Ionogels

Abstract: In this study, an ionic liquid (IL), 1-butyl-3-methylimidazolium acetate, was used to prepare ionogels with microcrystalline cellulose (MCC) and halloysite (Hal). SEM, XRD, TG, DSC, FTIR spectroscopy, conductometry and mechanical tests were used to study the morphology, structure, thermal behaviour and electrophysical and mechanical characteristics of synthesised ionogels. XRD analysis showed a slight decrease in the interlayer space of halloysite in ionogels containing MCC, which may have been associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
2
1
Order By: Relevance
“…For example, the T g value became almost 12 • C higher compared to the ionic liquid. A similar conclusion concerning the influence of the clay mineral was made by us earlier for the BMImAc/Halloysite ionogels [26] as well as for the BMImNTf 2 /Bent and BMImNTf 2 /Na-MMT ionogels [36]. The presented data indicate the confinement in the IL/clay systems.…”
Section: Phase Transitions In the Bmimac/na-bent/mcc Ionogelssupporting
confidence: 90%
See 2 more Smart Citations
“…For example, the T g value became almost 12 • C higher compared to the ionic liquid. A similar conclusion concerning the influence of the clay mineral was made by us earlier for the BMImAc/Halloysite ionogels [26] as well as for the BMImNTf 2 /Bent and BMImNTf 2 /Na-MMT ionogels [36]. The presented data indicate the confinement in the IL/clay systems.…”
Section: Phase Transitions In the Bmimac/na-bent/mcc Ionogelssupporting
confidence: 90%
“…The presented data indicate that the interaction with bentonite nanoparticles hinders the decomposition of the IL molecules. It should be noted that earlier [26], when studying the thermal behavior of the BMI-mAc/Halloysite composites, we made the opposite conclusion. Namely, we reported that BMImAc confined in the halloysite nanotubes decomposed easier than bulk IL.…”
Section: Thermal Decomposition Of Starting Materials and Ionogels Bmi...contrasting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, when exfoliated, their structured aluminosilicate layers provide high gravimetric surface area that results in robust nanocomposite mechanical properties . The most common clays utilized are montmorillonite, vermiculite, and halloysite for nanofillers or matrices in polymer, polymer gel, and ionogel electrolytes. In these cases, the nanoclay provides mechanical support, increasing the electrolyte mechanical modulus and decreasing polymer crystallinity that enhances ionic conductivity. , Despite the breadth of demonstrated clay nanocomposite electrolytes, the most naturally abundant clay variety, kaolinite, has rarely been utilized. , The 1:1 structure of silica and alumina layers within bulk kaolinite results in strong hydrogen bonding between the layers making exfoliation difficult relative to other clay varieties. , Although kaolinite nanocomposites produced through chemical intercalation have been demonstrated, this process is time-intensive and limited to a small subset of molecules, restricting potential applications. , Only one reported system to date has shown direct liquid-phase exfoliation of kaolinite, albeit with the assistance of a large fraction of graphene oxide (GO) dispersing agent (i.e., 5:1 GO/kaolinite) and no reported yield for the process. , Therefore, a need remains for a highly scalable kaolinite exfoliation process that will enable broader use of kaolinite in SSEs and related clay nanocomposite applications.…”
Section: Introductionmentioning
confidence: 99%